Scenarios for the future of mental health care: a social perspective. (March 2017) - Giacco, Domenico; Amering, Michaela; Bird, Victoria; Craig, Thomas; Ducci, Giuseppe; Gallinat, Jürgen; Gillard, Steven George; Greacen, Tim; Hadridge, Phil; Johnson, Sonia; Jovanovic, Nikolina; Laugharne, Richard; et al.
Summary: Social values and concepts have played a central role in the history of mental health care. They have driven major reforms and guided the development of various treatment models. Although social values and concepts have been important for mental health care in the past, this Personal View addresses what their role might be in the future. We (DG, PH, and SP) did a survey of professional stakeholders and then used a scenario planning technique in an international expert workshop to address this question. The workshop developed four distinct but not mutually exclusive scenarios in which the social aspect is central: mental health care will be patient controlled; it will target people's social context to improve their mental health; it will become virtual; and access to care will be regulated on the basis of social disadvantage. These scenarios are not intended as fixed depictions of what will happen. They could, however, be useful in guiding further debate, research, and innovation.